Decoding Suicide: The Need For Mandatory Psychological Autopsy In India (Journal of Forensic Medicine & Toxicology, 2026)
Suicide remains a major public health and medico-legal challenge in India, where rates are among the highest globally.  Traditional autopsy often fails to distinguish suicide from accident or homicide in equivocal cases, leading to diagnostic  and legal uncertainty. The psychological autopsy (PA), developed in the mid-20th century, reconstructs the deceased’s  mental state and life stressors through collateral interviews and records. This paper reviews the concept, history, methodology, applications, and legal-ethical considerations of Psychological Autopsy, with emphasis on its relevance in India.  Landmark international and Indian cases highlight its investigative value. Ethical implications after the introduction  of the Bharatiya Nyaya Sanhita (BNS), Bharatiya Nagarik Suraksha Sanhita (BNSS), and Bharatiya Sakshya Adhiniyam  (BSA) are examined. Finally, we argue for PA’s mandatory integration into medico-legal practice in India to strengthen  forensic investigation, judicial outcomes, and suicide prevention strategies.
Keywords: Psychological autopsy; Suicide; Medico-legal investigation.